(untitled) (DEPAN, 2025)
This study investigates the factors influencing the entrepreneurial intentions of business students, specifically focusing on the roles of locus of control, social networks, and creativity. The primary objective is to examine how these key factors locus of control, social networks, and creativity affect the entrepreneurial intentions of management students in constituent colleges within the Kathmandu Valley. A descriptive and correlational research design was adopted. Data were collected from 324 business students at Tribhuvan University, of which 252 responses were deemed valid for analysis. The data were analyzed using SPSS version 25, employing descriptive statistics, correlation coefficients, and multiple regression analysis. The findings revealed that both locus of control and social networks had a significant positive impact on the entrepreneurial intentions of management students. However, creativity did not show a significant relationship with entrepreneurial intention. These results underline the importance of strengthening students’ internal locus of control and social networking skills to enhance their entrepreneurial mindset. The lack of a significant connection between creativity and entrepreneurial intention suggests a need for further exploration into how creativity is perceived and utilized within the Nepali context. Overall, the study provides meaningful insights for researchers, educators, and policymakers working to foster entrepreneurship among university students in Nepal. It also recommends revising entrepreneurship curricula to include more experiential learning opportunities that enhance self-confidence and encourage real-world engagement.